Automatic Ventilation Control System for Energy Efficient Buildings using CO2 Sensors - Rupam S, Rote; Rupali R, Jagtap (International Journal of Computer Sciences and Engineering, 2025)
In this paper, the proposed work states automatic control strategy for ventilation systems in energy-efficient buildings. To maintain indoor CO2 in the comfort zone to the accurate level and minimum ventilation rate is the main design goal of automatic ventilation controller. The system uses CO2 as the main indicator of human comfort. The intelligent system as compared to traditional ON/OFF or fixed ventilation system gives better results in energy saving and also provide high indoor air quality. The technical notes provide the block diagram description and the importance using AVR Microcontroller. The KEIL µVision3 makes Embedded C Programming much easier than KEIL µVision2.